ANALISIS PENDAPATAN USAHATANI PADI SAWAH DI DESA BUYUMPONDOLI KECAMATAN PAMONA PUSELEMBA KABUPATEN POSO - Atnan, Atnan; Tangkesalu, Dance (AGROTEKBIS, 2017)
This study aimed to determine the income of wetland rice farming in Buyumpondoli Village. The location of the research was purposively determined with 38 respondents selected from 250 farmers using the Slovin formula. The analysis used was the analysis of income. The analysis showed that the average rice production was 4793.51 kg/1.02ha or 4699.52kg/ha. The average revenue of the rice farming was IDR 28,761,081.08/1.02ha or IDR 28,197,138.31/ha with the average total cost of IDR 11,024,175.68/1.02ha or IDR 10,808,015.37/ha and the average income of IDR 17,653,229.73/ha or IDR 17,307,087.97/ha.Â Key Words : Income, Rice, wetland.